Efficacy and safety of nintedanib for pulmonary fibrosis in severe pneumonia induced by COVID-19: An interventional study. (July 2021) - Umemura, Yutaka; Mitsuyama, Yumi; Minami, Kensuke; Nishida, Takeshi; Watanabe, Atsushi; Okada, Naoki; Yamakawa, Kazuma; Nochioka, Kotaro; Fujimi, Satoshi
Abstract: Objectives: One of the most significant features of poor prognosis in COVID-19 is pulmonary fibrosis. Nintedanib is a new antifibrotic agent that interferes with processes of pulmonary fibrosis. This study aimed to investigate the efficacy and safety of nintedanib in COVID-19. Methods: This was an interventional study in which adult patients with COVID-19 requiring mechanical ventilation were consecutively enrolled. The primary endpoint was 28-day mortality after the initiation of mechanical ventilation. The secondary endpoints were length of mechanical ventilation, volume of lung injury, and the incidence of gastrointestinal adverse events and acute liver failure. Results: Thirty patients with COVID-19 underwent nintedanib therapy. We included 30 patients not receiving nintedanib as the historical control group. There were no significant differences in 28-day mortality between the groups (23.3% vs 20%, P  = 0.834). Lengths of mechanical ventilation were significantly shorter in the nintedanib group ( P  = 0.046). Computed tomography volumetry showed that the percentages of high-attenuation areas were significantly lower in the nintedanib group at liberation from mechanical ventilation (38.7% vs 25.7%, P  = 0.027). There were no significant differences in the adverse events. Conclusions: The administration of nintedanib may offer potential benefits for minimizing lung injury in COVID-19.